(untitled) (Research, Society and Development, 2020)
Objective: This study aimed at identifying scientific publications on preceptor training in multiprofessional or uniprofessional health residency. Methods: Integrative review with searches on Web of Science, Scopus, ScienceDirect, Pubmed, Scielo, and Lilacs databases considering articles published between 2015 and 2019. Results: 21 publications were selected for the study, out of which 12 were Brazilian; the other 9 were foreign, using English as the predominant language on 67% of the publications. The publications presented are all in the fields of Pharmacy and Nursing, and only 7 articles were fully devoted to the theme ‘training strategies’. The articles were sorted out into 4 preceptor training-related topics: strategies for preceptor training, preceptor training for interdisciplinarity, accountability for preceptor training and necessity of preceptorship training. Conclusions: The study has demonstrated that preceptorship training is important for the qualification of health services, yet residency programs are still weak in carrying it out. That indicates a gap to be filled in the health training scenario and on scientific publications.